2013
DOI: 10.3892/or.2013.2711
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Citrus unshiu Marc. inhibit cancer cell adhesion to endothelial cells by selective inhibition of VCAM-1

Abstract: Abstract. Citrus fruits have been used as edible fruit and a component of traditional medicine for various diseases including cancer since ancient times. Herein, we investigated the anticancer activity of flavonoids of Citrus unshiu Marc. (FCM) focusing on anti-metastatic effects. We prepared FCM and performed experiments using MDA-MB-231 human breast cancer cells. FCM inhibited TNF-induced cancer cell adhesion to human umbilical vein endothelial cells (HUVECs) without showing any toxicity. FCM inhibited the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…In addition, Kim et al (32) reported that C. unshiu peel reduces systemic inflammation in tumor-bearing mice and inhibits the production of pro-cacheche factors in tumors with the prevention of skeletal muscle atrophy and weight loss. It has also been reported that polysaccharides or flavonoids found in the C. unshiu peel can inhibit the metastasis of cancer cells (33,34); however, the evidence for the therapeutic potentials of C. unshiu peel against human cancer cells and the molecular pathways involved in suppression of cancer cell apoptosis remain unclear. Therefore, we investigated the anti-cancer effects of ethanol extract of C. unshiu peel (EECU) in human bladder cancer T24 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kim et al (32) reported that C. unshiu peel reduces systemic inflammation in tumor-bearing mice and inhibits the production of pro-cacheche factors in tumors with the prevention of skeletal muscle atrophy and weight loss. It has also been reported that polysaccharides or flavonoids found in the C. unshiu peel can inhibit the metastasis of cancer cells (33,34); however, the evidence for the therapeutic potentials of C. unshiu peel against human cancer cells and the molecular pathways involved in suppression of cancer cell apoptosis remain unclear. Therefore, we investigated the anti-cancer effects of ethanol extract of C. unshiu peel (EECU) in human bladder cancer T24 cells.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are known to have various health beneficial effects on the human body too. Some of the benefits attributed to flavonoids include anti‐oxidant, anti‐allergic, anti‐cancer, anti‐inflammatory, and anti‐virus activities (Nijveldt and others ; Jin and others ; Tanaka ). A number of different mechanisms may be involved in such biological activities of flavonoids through radical scavenging action and association with different endogenous protein (Cho and others ; Du and others ).…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive compounds of CU peel are well-known to contain flavonoids, such as naringin, hesperidin, and nobiletin, and the plant cell barrier component and its anticancer effect are also well known (Jin et al, 2013;Kim et al, 2015;Park et al, 2018;Shin, Park, & Shin, 2018). Our previous study reported that water extract of CU peel contained the reference flavonoids (i.e., naringin, hesperidin, and neohesperidin) and had anticancer potential (Kim, Bo, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Lee et al, (Lee, Lee, Kim, & Kim, ), fermented extract of CU peel inhibited the growth of human pancreatic cancer cells via the induction of caspase‐3 cleavage. In 2011, one study reported CU has an antitumor effect through enhancing immune‐mediated cytokines in murine renal carcinoma cells (Lee et al, ); Jin et al () suggested that phytochemicals from CU inhibit cell adhesion and invasion in human breast cancer cells. Our previous studies also clearly demonstrated that water and ethanol extracts of CU peel have anticancer effect via the involvement of reactive oxygen species (ROS)–dependent activation of adenosine monophosphate‐activated kinase in human breast cancer MCF‐7 cells (Kim et al, ; Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%